Aplicación de la cooperación eficaz y su incidencia en los delitos vinculados al crimen organizado. - Valencia Del Pozo Jessica Gabriela (2024)
The purpose of this research work is to determine the effectiveness of the application of effective cooperation since it has been included in the Ecuadorian criminal procedural legislation currently governed by the Comprehensive Organic Criminal Code, which has been conceived as an investigation and sanction technique for have a direct relationship with the investigation and punishment of crimes related to organized crime. The complexity of determining a criminal organization depends substantially on a possible effective informer or cooperator from dogmatic, legal and jurisprudential treatment, which is not a new figure within the adjective criminal legislation of modern states and the accusatory procedural system. which also has not been truly applied to punish crimes related to a crime that increasingly acts with more violence and sophistication. Due to the above, the following research is presented that allows us to consider the dogmatic conceptions, which have stood out in the use of this procedural figure and its legal-legal treatment that necessarily merit consideration as its effectiveness in the fight against organized crime that is currently being carried out. has delved deeper into Ecuadorian society. The methodology used in this research is intended to give it a qualitative approach given that the type of research is non-experimental in nature and remains a pure or basic research, since to treat legal-criminal sciences, it is necessary to be able to maintain . in the review of the literature of criminal sciences, from its adjective procedural perspective, as well as its effectiveness and relevance in the current Ecuadorian criminal process. 5 The figure of effective cooperation can become transcendental with proper application, since it basically deals with the repentance of one of the participants in the criminal organization, which becomes an informer of the crime of which it contributes with precise information that is countered and verified, but adequate legal treatment is not always given; and its improper application can transgress fundamental rights and principles of due criminal process.